A High-Input Voltage Two-Phase Series-Capacitor DC-DC Buck Converter. (8th June 2020) - Ahmed Rmila, Salahaldein; Ang, Simon S.
Abstract : A high-input voltage 2-phase series-capacitor (2- pscB ) DC-DC buck converter is theoretically analyzed, designed, and implemented. A new design approach for an automatic current sharing scheme was presented for a 2-phase series-capacitor synchronous buck converter. The series-capacitor voltage is used to achieve current sharing between phases without a current sensing circuit or external control loop as each phase inductor charges and discharges the series capacitor to maintain its average capacitor voltage constant. A novel isolated gate driver circuit to accommodate an energy storage capacitor is proposed to deliver isolated gate voltages to the switching transistors. An I 2 control scheme that uses only one feedback path control for the four gate drivers is proposed to enable higher voltage conversion. An experimental 110-12 V 6 A load prototype converter was designed, and its current sharing characteristics were experimentally verified.